Assessment of impression material accuracy in complete-arch restorations on four implants - Baldissara, Paolo; Koci, Brunilda; Messias, Aion Mangino [UNESP]; Meneghello, Roberto; Ghelli, Francesco; Gatto, Maria Rosaria; Ciocca, Leonardo (Elsevier, 2021)
Statement of problem: New polyvinyl siloxane (PVS) materials with enhanced properties have been developed to improve and facilitate implant impression techniques. However, studies on their accuracy are lacking. Purpose: The purpose of this in vitro study was to determine the accuracy and precision of implant impressions made with some recently introduced materials on a simulated patient requiring an all-on-4 implant-supported prosthesis. Well-established polyether materials were also evaluated as a comparison. The variables considered were material type, consistency, splinting or not splinting techniques, and implant angulation. Material and methods: A reference master model was made by inserting 4 implants at angles of 0, 5, and 10 degrees. Eighty impressions were made at 37 °C in wet conditions by using a standardized technique. Eight groups (n=10) were created using monophasic, single-viscosity materials (Hydrorise Implant Medium, HIM-ns; Hydrorise Implant Medium, HIM; Honigum Mono, HM; Impregum, IMP), and 2-viscosity materials (Hydrorise Implant Heavy+Light-ns, HIH+L-ns; Hydrorise Implant Heavy+Light, HIH+L; Honigum Heavy+Light, HH+L; and Permadyne and Garant [Heavy+Light, PeH+L]). Hydrorise materials were used with splinting and not splinting (ns) techniques. The reference points located on the connecting platforms of the transfer copings (TCP) were compared with the same points on the implant connecting platforms (ICP) located in the reference model. The accuracy and precision of the impressions were determined as linear 3D errors and standard deviation between each TCP-ICP couple by using an optical coordinate measuring machine (OCMM). Results: PVS materials were generally better than polyether materials, with Hydrorise materials (HIM and HIH+L) showing significantly better accuracy and precision (30.9 ±14.4 μm and 28.7 ±15.5 μm, respectively) than IMP and PeH+L polyethers (44.2 ±16 μm and 43.8 ±17.6 μm, respectively; P<.001). Honigum materials were statistically similar to Hydrorise materials (P=.765). The values shown by Hydrorise nonsplinted groups (HIH+L-ns and HIM-ns) were not statistically different from those of the splinted polyether impressions (P=.386). The viscosities (monophasic or heavy+light) had no effect on accuracy, but monophasic material positively influenced precision (HIM and HIH+L, P=.001). No correlation was found between implant angulation and accuracy (multilevel analysis and Kendall rank correlation coefficient=-0.065; P=.133). Conclusions: Recently introduced materials designed for implant impressions showed significantly higher accuracy and precision; even with the unfavorable nonsplinting technique, the new materials performed similarly to, or better than, polyether materials. Although the transfer coping splinting technique generally improved the accuracy and precision of Hydrorise materials, the effect was significant only within HIH+L groups.